BACTERIAL CONTAMINATION OF IRAQI PAPER CURRENCY NOTES IN CIRCULATION & RESISTANCE OF PATHOGENIC BACTERIA TO ANTIBIOTICS - abid, huda (Iraqi Journal of Science, 2024)
The present study was carried out to determine the type and nature of bacterial contamination of Iraqi paper currency notes (Dinar) in circulation. 100 paper currency notes of different denominations were randomly collected from different places and different occupational groups in Baghdad city. Identification and characterization results showed bacterial contamination of all 100 samples with 100% contamination. A total of 114 bacterial isolates were obtained from the one hundred samples made up of 12 different bacterial species. Bacteria isolated from Iraqi paper currency notes include: Bacillus spp. (28.1%) ،Coagulase negative Staphylococci (21.1%), Staphylococcus aureus (7.9%) ،Proteus spp. (7.9%), Escherichia coli (6.1%),Citrobacter spp. (6.1%) ،Klebsiella spp. (5.3%) ،Pseudomonas aeruginosa (4.4%),Enterobacter spp. (4.4%), Salmonella spp. (3.5%),β- hemolytic Streptococcus (3.5%),α- hemolytic Streptococcus (1.8%). All the denominations were contaminated with Bacillus spp. And Coagulase negative Staphylococci, also the small denominations were more contaminated than high denominations. The antibiotic susceptibility patterns of pathogenic bacteria isolated from Iraqi paper currency notes showed resistance to some used antibiotics with different percentage.